Gastro-Esophageal Reflux Is Not a Common Cause of Chronic Cough; A Singapore Case Series - Vijo Poulose (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Gastro-esophageal reflux disease (GERD) is believed to be a common cause of chronic cough. There is a paucity of data on GERD-related cough (GERC) from Singapore. Our aim was to examine the prevalence, demographics and clinical features of GERC patients seen in a large teaching hospital in Singapore.Methods: We did a retrospective review of patients referred to the respiratory clinic for evaluation of chronic cough (≥ 6 weeks in duration). All patients diagnosed with GERC were further classified into 2 groups based on the likelihood of esophageal reflux being the cause of cough. 1) Likely GERC and 2) Possible GERC. We describe the demographics, clinical characteristics and the outcomes of these patients.Results: Of the 330 chronic cough patients seen over a 6 years period, 45 patients (13%) were diagnosed with GERC. Most were women (69%), the median age was 53 years and the median duration of symptoms was 26 weeks. Fourteen patients were in the Likely group and 31 in the Possible group. Throat symptoms or signs were found in 77 % of patients.Conclusions: Amongst patients referred for cough to a specialist clinic, GERD was not seen as a common cause. Throat signs and symptoms were common and could add weight to the diagnosis of GERC. There was no particular timing for the cough with regards to day or night.